Use of Fertility Awareness-Based Methods for Pregnancy Prevention Among Ghanaian Women: A Nationally Representative Cross-Sectional Survey - Polis, Chelsea B. (Glob Health Sci Pract, 2021)
Few studies in low- and middle-income countries have examined the use of fertility awareness-based methods (FABMs) for pregnancy prevention. Understanding the prevalence of FABM use among Ghanaian contraceptors and the characteristics and practices of users is essential. Our 2018 nationally representative survey of Ghanaian women included detailed questions on the use of rhythm and Standard Days Method/Cycle Beads (SDM). After considering multimethod use patterns, we estimated likely FABM prevalence among contraceptors, identified characteristics associated with current use of an FABM (vs. current use of a hormonal method/intrauterine device [IUD]), and described how women report using FABMs. At least 18% of contracepting Ghanaian women likely use an FABM, though this may be underreported. Among FABM users, 57% reported current use of an FABM alone; the remainder reported concurrent use of other methods. Women who were older, richer, more educated, and had fewer children had higher odds of current FABM use versus IUD/hormonal method. Although FABM users were more likely than other contraceptors to correctly identify the approximate fertile time, only 50% of FABM users did so correctly. Most (92%) rhythm users were interested in making their method use more effective. While 72% had heard of SDM, less than 25% had heard of various other ways to make the rhythm method more effective. Only 17% of rhythm users had ever discussed the method with a health professional. Rhythm users indicated substantial willingness to track additional biomarkers (e.g., daily temperature or cervical mucus) or to use a phone to enhance the effectiveness of their method, and most indicated no substantial difficulty getting partners to abstain or withdraw on fertile days. A nontrivial proportion of reproductive age Ghanaian women are using an FABM, nearly all of whom are interested in learning how to improve its effectiveness. The family planning field should better address these women's contraceptive needs in commitment to reproductive autonomy and choice.